ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN MEMBELI PRODUK PADA CV APOLLO MOTOR TANJUNG MORAWA - Halim Loly; Rudy Halim (Politeknik Negeri Sriwijaya, 2014)
The purpose of this study was to determine the influence of price and quality product to purchasing decisions on CV Apollo Motor Tanjung Morawa. The type of research used in this study is associative causal quantitative approach. Associative causal research is a research that aims to determine the relationship between two or more variables, while the quantitative approach used in this study because the data expressed in numbers, when a series of observations or measurements can be expressed in numbers. Data analysis method used is multiple linear regression. The population in this study was the overall customer of CV Apollo Motor Tanjung Morawa as many as 1312 which are the consumers who make purchases from January 2012 to June 2012. Determination of the sample in this study using the formula Slovin with samples are 93 people. The results showed that the price variable (X1) and product quality (X2) have effect on the purchase decision variable (Y) in CV Apollo Motor Tanjung Morawa by 96.3%. While the remaining 3.7% is the influence of the other independent variables were not examined in this study.